The Apparent metabolizable energy and apparent metabolizable energy corrected for nitrogen balance of amaranth grains for Japanese quails (Coturnix coturnix japonica) - QUIRINO, CAIO SILVA; LIMA, HEDER JOSÉ D’AVILA; MORAIS, MARCOS VINÍCIUS MARTINS; AMARAL, ELIEVERSON FIRMIANI DE FREITAS; BITTENCOURT, TATIANA MARQUES; MARTINEZ, JULIANA FREITAS; PEREIRA, ISABELLI DIAS BRITO (The Indian Journal of Animal Sciences, 2023)
The objective was to determine the values of apparent metabolizable energy (AME) and apparent metabolizable energy corrected for nitrogen balance (AMEn) of roasted and in natura amaranth grains. A breeding stock of 108 female Japanese quails (Coturnix coturnix japonica) with an initial age of 29 days was used. The birds were distributed in a completely randomized design with three treatments and six replications, with six quails per experimental unit. The treatments used were reference diet, reference diet + 30% in natura amaranth and reference diet + 30% roasted amaranth. The variables evaluated were feed intake, body weight variation, retained nitrogen, retained crude protein, dry matter digestibility and crude protein. Higher values of AME and AMEn were verified for the roasted amaranth grains, in relation to the in natura grains. There was no verification regarding the influence of amaranth grains, both roasted and in natura, for the variables feed intake, body weight variation, retained nitrogen, retained crude protein, dry matter and crude protein digestibility. It was concluded that the in natura amaranth grains provided 3888 kcal/ kg of AME and 3352 kcal/kg of AMEn, while the roasted amaranth grains provided 4044 kcal/kg of AME and 4028 kcal/kg of AMEn.